Diagenesis, coalification, and hydrocarbon generation of the Keruh Formation, In Kuantan-Singingi Area, Central Sumatera, Indonesia - Rahmat Heryanto (Jurnal Geologi dan Sumberdaya Mineral, 2006)
The Eocene-Oligocene Keruh Formation is exposed in the western part of Kuantan-Singingi area, southwest margin of the Central Sumatera Basin. It is correlated to the Pematang Group in another part of the Central Sumatra Basin and is also to the Kelesa Formation in the Tigapuluh Mountains. The formation is composed of conglomerate and well-bedded sandstone in the lower part, interbedded mudstone and coal seams in the middle part, and mainly made up of laminated to well bedded light-dark grey to blackish organic-rich mudstones in the upper part of succession. It was deposited in a fluviatiIe to a lacustrine environment with some marine condition influences.Diagenetic processes which occurred in the Keruh Formation are compaction and formation of authigenic mineral and secondary porosity. The compaction effects are illustrated by the presence of bending of mica flakes and by grains supported fabrics with long grain contact as well as clay mineral oriented. The formation of the authigenic minerals is recorded by the presence of authigenic quartz and clay minerals, and also quartz overgrowths. The secondary porosity occurrence is caused by a dissolution of the feldspar and clay minerals. The diagenetic stage of the Keruh Formation is included into a mesogeneticsemi-mature to mature "A" which equal to mudrock stage II.Based on the maturity of this Formation reflectance within dispersed organic matter (d.o.m.) and coal of the Keruh Formation, the naturity of this Formation is included into an immature to early mature stage, whereas based on the T max and Hydrogen Index (HI)  values, the kerogen With Formation is categorized Into a late immature to early mature level.There Is a relationship between diagenetic stage and maturation of organic matter which was caused by the burial history with the depth of buriaI between 2000 to 3000. m, which  produced the paIeo temperature of 65° to 95°C.Keywords: Keruh Formation, diageneses, authigenic mineral, thermal maturation